Postoperative “Chimney” for Unintentional Renal Artery Occlusion after EVAR - Marco Franchin; Federico Fontana; Filippo Piacentino; Matteo Tozzi; Gabriele Piffaretti (Case Reports in Vascular Medicine)
Renal artery obstruction during endovascular repair of abdominal aortic aneurysm using standard device is a rare but life-threatening complication and should be recognized and repaired rapidly in order to maintain renal function. Both conventional surgery and endovascular stenting have been reported. We report a case of late postoperative bilateral “chimney” to resolve a bilateral thrombosis of the renal artery following an uncomplicated endovascular aortic repair.